Spectrophotometric Determination of Ascorbic Acid in Aqueous Solutions - Fadhel, Dhuha Hashem (Al-Nahrain Journal of Science, 2012)
Anew spectrophotometeric method for determination of ascorbic acid(A.A) in aqueous solutions depending on its ability to reduce the colors of permanganate at (530nm) and dichromate at (350 nm). The optimum conditions such as best concentration of reactant and order of addition were studied to get the highest sensitivity (ε=2355.70 and 3094.75) L.mol-1.cm-1 with wide range of calibration curves (1-16) and (2-90) ppm good repeatability (RSD% 0.73 and 1.49), the recovery %(100.20 and 99.42), Erel% (-0.20 and 0.58) for gave, Pharmaceutically prepared tablets were measured with the new technique using Standard Addition Method given a very good recovery % (101.25 and 98.75) with a small Erel% (-1.25 and 1.25).